Budaya Hukum sebagai Faktor Pendorong Terwujudnya Reformasi Birokrasi Daerah di Indonesia - Jamiat Akadol (Jurnal Magister Hukum Udayana, 2018)
The purpose of this research is to know the legal culture as the driving factor of the realization of regional bureaucracy reform in Indonesia. The method used is the method of normative juridical research with conceptual approaches, legislation, and case approach. Various cases of corruption and very bad service in investment activities have hindered and even damaged the image of the Indonesian nation even in today's highly dynamic world. The bureaucratic legal culture is considered the main factor causing such bad bureaucratic behavior. The legal culture of the royal heritage that is only devoted to highways is difficult to remove from bureaucratic behavior. Cultural heritage, was fertile in the new order era, even in the current reform era. Through the optimization of local culture combined with the autonomy and decentralization policy implemented with the principle of autonomy as widely as possible, it can be attempted to overcome the negative culture of bureaucratic culture into a bureaucracy that eventually can be realized good governance.